2015
DOI: 10.1007/s13203-015-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-alumina as active matrix added to HZSM-5 catalyst on the aromatization of methanol

Abstract: HZSM-5-based catalyst is a recognized catalyst which is particularly selective towards the formations of aromatics in the methanol reaction. However, studies on HZSM-5-based catalyst were mainly focused on the addition of metallic or/and nonmetallic element. Quite few studies have reported the effect of active matrix such as calumina on the aromatization of methanol. In this study, calumina was introduced into HZSM-5-based catalyst for the purpose of investigating the effect of c-alumina in methanol to aromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It was generally observed that the Bronsted acidity decreased as metal loading increased on parent ZSM-5. This was due to replacement of Bronsted sites by the added metals on the surface of the catalyst having a significant effect on activity test for propane aromatization [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…It was generally observed that the Bronsted acidity decreased as metal loading increased on parent ZSM-5. This was due to replacement of Bronsted sites by the added metals on the surface of the catalyst having a significant effect on activity test for propane aromatization [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Inoue et al 51 reported that Ag doping improved the alkenes' dehydrogenation of zeolite catalysts and more alkenes and bio-aromatics are produced. Chen et al 52 prepared the γ-alumina modification HZSM-5 catalysts to obtain the high yield of bio-aromatics, in which the modification of γ-alumina can increase the Lewis acid site concentration, acid strength, and pore size of the HZSM-5 catalyst. It is worth noting that the coking of the zeolite catalysts should be resolved during the BMTA process.…”
Section: Synthesis Routes Of Bio-aromaticsmentioning
confidence: 99%
“…However, an increased aromatisation degree produces more heavy products and, therefore, deactivation of the catalyst occurs by coking . Chen and co‐workers achieved an increase in both concentration of Lewis acid sites, acid strength and pore size by simply mixing γ‐alumina with ZSM‐5, which promoted the production of aromatics.…”
Section: Methanol To Aromaticsmentioning
confidence: 99%
“…[15c] However, an increased aromatisation degree produces more heavy products and, therefore, deactivation of the catalyst occurs by coking. [15e] Chen and co-workers [18] achieved an increasei nb oth concentration of Lewis acid sites, acid strength and pore size by simply mixing g-alumina with ZSM-5, which promoted the production of aromatics. All of the above-mentioned research reported high yields of p-xylene among the aromaticf raction;h owever,several studies concentrated specifically on this targetm olecule.…”
Section: Methanol To Aromaticsmentioning
confidence: 99%